In vitro antitumor activity evaluation of some 1,2,4-triazine derivatives bearing piperazine amide moiety against breast cancer cells - Yurttaş, Leyla; Demirayak, Şeref; Ilgın, Sinem; Atlı, Özlem (Elsevier Ltd, 2014)
A series of 1,2,4-triazine derivatives bearing piperazine amide moiety has been synthesized and investigated for their potential anticancer activities. 1-[4-(5,6-Bis (4-subtituted phenyl) -1,2,4-triazin-3-yl)piperazin-1-yl]-2-[4-(3-substituted phenyl) piperazin-1-yl]ethanone derivative (1-32) compounds were synthesized by a four step synthetic procedure. The activity studies were evaluated using XTT method, BrdU method and flow cytometric analysis on MCF-7 breast cancer cells and NIH/3T3 (mouse embryonic fibroblast cells) healthy cells. Compounds 5 with 3-chlorophenyl and compound 7 with 4-chlorophenyl substitutions were found to be promising antiproliferative agents comparing with an effective anticancer drug, cisplatin.
Keywords: 1,2,4-Triazine; Antiproliferative Activity; Apoptosis; Breast Cancer; Piperazine Amide; XTT Method